Using Nanotech Radiopharmaceutical for the Visualization of Sentinel Lymph Nodes in Patients with Larynx and Hypopharynx Cancer; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Sinilkin I. G. Ivan Gennadjevich; Chernov V. I. Vladimir Ivanovich; Choynzonov E. T.; Chijevskaya S.; Titskaya А. А. Anna Aleksndrovna; Zelchan R. V. Roman Vladimirovich (Radiation Technologies in Medicine, 2015)
Title screen